2012
DOI: 10.1021/mp300172e
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Designed Aberrant Kinase-Targeted Endogenous Protein Nanomedicine against Oncogene Mutated/Amplified Refractory Chronic Myeloid Leukemia

Abstract: Deregulated protein kinases play a very critical role in tumorigenesis, metastasis, and drug resistance of cancer. Although molecularly targeted small molecule kinase inhibitors (SMI) are effective against many types of cancer, point mutations in the kinase domain impart drug resistance, a major challenge in the clinic. A classic example is chronic myeloid leukemia (CML) caused by BCR-ABL fusion protein, wherein a BCR-ABL kinase inhibitor, imatinib (IM), was highly successful in the early chronic phase of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Conjugating artemisinin to a TfR targeting peptide shows anti-leukemia activity with a significantly improved leukemia cell selectivity [128]. With the development of technology, some carriers have been developed to link ligands and therapeutic agents for improving the efficacy and safety in therapeutic agent delivery, among which liposomes, dendritic molecules and nanoparticles have been widely used [129, 130]. A human serum albumin based nanomedicine, which is loaded with sorafenib and conjugated ligands for TfR specific delivery, can play enhanced anti-leukemia activity in drug resistant CML patient samples [130].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugating artemisinin to a TfR targeting peptide shows anti-leukemia activity with a significantly improved leukemia cell selectivity [128]. With the development of technology, some carriers have been developed to link ligands and therapeutic agents for improving the efficacy and safety in therapeutic agent delivery, among which liposomes, dendritic molecules and nanoparticles have been widely used [129, 130]. A human serum albumin based nanomedicine, which is loaded with sorafenib and conjugated ligands for TfR specific delivery, can play enhanced anti-leukemia activity in drug resistant CML patient samples [130].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of technology, some carriers have been developed to link ligands and therapeutic agents for improving the efficacy and safety in therapeutic agent delivery, among which liposomes, dendritic molecules and nanoparticles have been widely used [129, 130]. A human serum albumin based nanomedicine, which is loaded with sorafenib and conjugated ligands for TfR specific delivery, can play enhanced anti-leukemia activity in drug resistant CML patient samples [130]. The sensitivity of leukemia cells to imatinib can also be enhanced by encapsulated with TfR targeted liposomes [131].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, pSTAT5 and antiapoptotic protein MCL-1 expressions were inhibited. This study revealed that, combining molecular diagnosis and personalized nanomedicines could have therapeutic functionality to endogenous proteins to overcome clinically important challenges like molecular drug resistance [120]. All these studies point out the importance of STAT5 from JAK/STAT pathway in CML treatment.…”
Section: Jak/stat Pathway and Treatment Strategiesmentioning
confidence: 79%
“…Patients need to be monitored every 3 months but in the case of serious patients monitoring need to be done every month. [1,5] Even though our patient was tested positive for BCR-ABL mutations, it is not known whether the mutation developed initially or after treatment with TKIs. Earlier detection of specific mutations might have prompted immediate new generation TKI therapy.…”
Section: Discussionmentioning
confidence: 92%